2004
DOI: 10.1007/s00540-004-0264-2
|View full text |Cite
|
Sign up to set email alerts
|

Laryngotracheal application of lidocaine spray increases the incidence of postoperative sore throat after total intravenous anesthesia

Abstract: We recommend that applications of lidocaine spray to the laryngotracheal area should be avoided to help eliminate unnecessary postoperative sore throat, thereby leading to improvement in patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
9
1
1
Order By: Relevance
“…Moreover, Oh et al [27] reported that preoperative 10% lidocaine spray to pharyngolaryngeal and intratracheal sites reduces the incidence of postoperative sorethroat. In the present study, 10% lidocaine spray did not cause any serious postoperative complications, and in contrast to the report by Maruyama et al [24], we were able to show that the incidence of postoperative sorethroat did not increase from the use of lidocaine spray.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, Oh et al [27] reported that preoperative 10% lidocaine spray to pharyngolaryngeal and intratracheal sites reduces the incidence of postoperative sorethroat. In the present study, 10% lidocaine spray did not cause any serious postoperative complications, and in contrast to the report by Maruyama et al [24], we were able to show that the incidence of postoperative sorethroat did not increase from the use of lidocaine spray.…”
Section: Discussioncontrasting
confidence: 99%
“…With respect to postoperative sorethroat occurring due to lidocaine spray, there have been conflicting results in previous reports. Maruyama et al [24] reported that when 8% lidocaine is sprayed before intubation, additives such as 1-menthol, ethanol, and alkalized solvents contained in lidocaine spray might add to the damage on the tracheal mucosa, thus leading to an increase in the incidence of postoperative sorethroat after total intravenous anesthesia. However, Herlevsen et al [25] showed that there was no significant correlation between lidocaine spray and incidence of postoperative sorethroat.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas inflation of the ETT cuff with lidocaine has been reported to alleviate postoperative sore throat, 8 application of lidocaine to the oropharyngeal cavity or laryngotracheal area seems to be ineffective. 9,10 Ketamine gargle has been suggested to reduce postoperative sore throat, but the systemic effect of ketamine may be of consequence. 3 Benzydamine hydrochloride (BH), a topical nonsteroidal anti-inflammatory drug (NSAID) with analgesic properties, has been reported to reduce the incidence and severity of postoperative sore throat when administered as an oral gargle or spray on the ETT cuff or oropharyngeal cavity.…”
Section: Résumémentioning
confidence: 99%
“…All have been shown to reduce the incidence and severity of POST upto 24 h postoperatively. [8] [7] Kori et al [9] and Maruyama et al [10] found higher incidence of POST in use of lignocaine jelly as lubricant jelly, so it was not used.…”
Section: Discussionmentioning
confidence: 99%